2016
DOI: 10.14739/2310-1237.2016.2.81333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunohistochemical characteristic of expression levels of Ki-67, p53, caspase 3 in non-invasive and invasive intestinal-type gastric adenocarcinoma

Abstract: Aim.Comparison analysis of expression levels of p53, and caspase 3 was performed between the tumor cells and the stromal cells of non-invasive intestinal-type gastric adenocarcinoma on the one hand and the tumor cells and the stromal cells of invasive intestinal-type gastric adenocarcinoma on the other hand.Materials and methods. For this purpose, pathohistological and immunohistochemical studies were used. The surgical material of 10 patients with non-invasive (pTis, pT1) intestinal-type gastric adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…According to the literature data p53 expression increases in the sequence «adenoma-carcinoma» [7,6,13,14]. In this study it was revealed that p53 expression by CRA epitheliocytes is 16,5 times higher than that for adenomas [39,67 (15,69; 83,75) % vs. 2,39 (1,58; 8,26) %, p˂0,05] and also is 40 times higher than that for hyperplastic polyps [39,67 (15, our colleagues: p53 expression increases in the sequence «hyperplastic polypdysplastic polypnon-invasive adenocarcinomainvasive adenocarcinoma» of the stomach [18,19]. Thereby, the results are consistent with current literature and indicate that CRA epitheliocytes distinguish by the prominent tendency to p53 accumulation, whereas epitheliocytes of benign polyps characterize by the low level of p53 expression.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…According to the literature data p53 expression increases in the sequence «adenoma-carcinoma» [7,6,13,14]. In this study it was revealed that p53 expression by CRA epitheliocytes is 16,5 times higher than that for adenomas [39,67 (15,69; 83,75) % vs. 2,39 (1,58; 8,26) %, p˂0,05] and also is 40 times higher than that for hyperplastic polyps [39,67 (15, our colleagues: p53 expression increases in the sequence «hyperplastic polypdysplastic polypnon-invasive adenocarcinomainvasive adenocarcinoma» of the stomach [18,19]. Thereby, the results are consistent with current literature and indicate that CRA epitheliocytes distinguish by the prominent tendency to p53 accumulation, whereas epitheliocytes of benign polyps characterize by the low level of p53 expression.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…ИГХ исследования применены в трепанобиоптатах печени для дифференциальной диагностики гепатоцеллюлярного, холангиоцеллюлярного рака и метастазов в печень других злокачественных опухолей без установленной первичной локализации; в трепанобиоптатах предстательной железы -для дифференциальной диагностики рака предстательной железы и простатической интраэпителиальной неоплазии; в трепанобиоптатах молочной железы -для диагностики основных типов рака молочной железы и персонифицированного прогнозирования его агрессивных свойств; в гастро-и колоно-биоптатах -для дифференциальной диагностики лимфом, нейроэндокринных опухолей, рака и полипов с тяжелой дисплазией; в трепанобиоптатах поджелудочной железы -для дифференциальной диагностики основных типов панкреатического рака и нейроэндокринных опухолей; в соскобах эндометриядля дифференциальной диагностики рака эндометрия, полипов с тяжелой дисплазией и атипической гиперплазии эндометрия у женщин в перименопаузальном периоде. Результаты этих исследований опубликованы нами и нашими сотрудниками ранее [3,4,5,6,7,8] В судебно-гистологическом отделении ЗОБСМЭ в 2016 году у 205 лиц, скоропостижно умерших дома от онкологических заболеваний, проведены гистологические исследования. При этом, у 18 (8,78%) скоропостижно умерших дома злокачественная опухоль с распространенными метастазами была диагностирована по результатам судебно-медицинского вскрытия и судебно-гистологического исследования.…”
Section: результаты исследования и их обсуждениеunclassified
“…В значительном числе работ приводятся противоречивые данные об экспрессии MMP-2 и MMP-9 в РЖ [2, [9][10][11][12][13]. В частности, доказано, что совместная активация MMP-2 и MMP-9 в РЖ обеспечивает деградацию базальных мембран и реализацию инвазивного потенциала рака [1][2]5,9,13]. Данные о прогностической ценности экспрессии MMP-2 в РЖ противоречивы: C.L.…”
Section: Introductionunclassified